On the non existence of cyclical food-consumption patterns in a model of non-addictive eating - Davide Dragone (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
In a paper previously published in this journal, Levy (2002) [Levy A., 2002, Rational eating: can it lead to overweightness or underweightness? Journal of Health Economics 21, 887.899] presents a model of rational non-addictive eating that is claimed to explain cyclical food-consumption patterns where binges and strict diets alternate. I show that the model admits no oscillation at all, as the unique internal steady state has saddle point stability.
Keywords: 330